A területi (gazdasági) fejlődés társadalmi hajtóerői és állami szabályozása - Bartke, István (Tér és Társadalom, 1994)
This study, after outlining the concept, the dynamic and static forms of the regional balance, examines the factors of the regional static balance and the general features of the state interventions done for the balanced development in three regional dimensions, based on the goals and the typical strategic directions. In the global (world-wide) space different cultures, principles and values have a serious impact on economic development. On the ground of economic development and other features different regions can be specified, ones that have special inner balance systems. Outer intervention in autonomous development can amount to the birth of inner strains. The second examined regional levei is the international integrations, namely the levet of the European Union. Within this, on the one hand, automatisms of regional approach function, on the basis of market mechanisms, on the other hand, common regional development policy have been made (since 1975). The appearance and solution of the regional strains is in connection with whether the European Union will deve lop in the future as a closed or open system. The original level of regional policies is the state level. The content of the goals of regional development depends on the types of regional strains (static lacks of balance) within the country, the pace and direction of the economic growth, the levei of economic development etc. The goals of regional development are often stated on grounds of contradictory criteria.